Peran Perguruan Muhammadiyah Mewujudkan Masyarakat Islam Yang Berkemajuan di Kota Tangerang - Zulpiqor, Zulpiqor; Tambunan, Amirsyah (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2023)
The study aims to analyze the role of Muhammadiyah universities in uncovering syncretictraditionalist Islam towards a modern Islamic society and progress in Tangerang City. Thisresearch method is descriptive qualitative, which provides a comprehensive picture based onthe results of observation techniques, interviews, and review of Muhammadiyah documents(literature) related to Muhammadiyah Universities and the concept of an advanced IslamicSociety. The results of this study show that the role of Muhammadiyah University in realizinga progressive Islamic society in Tangerang City has a strategic role in developing Islamicda'wah progress to the community, not only providing spiritual guidance but also variousaspects of life such as the cultivation of intellectual values and morality that spur communitylife to rise from adversity due to weak practice of Islam among the community.Keywords: College, Muhammadiyah, Progress